Implementasi UU No 22 Tahun 2009 Pasal 131 Terkait Pemenuhan Hak Pejalan Kaki di Kota Pematang Siantar dalam Perspektif Siyasah Dusturiyah - Fidyan Hamdi Lubis; A Sudirman Suparmin (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2025)
Fulfillment of rights for citizens is an order ordered by the constitution for the government of the Republic of Indonesia. Fulfillment of pedestrian rights is one of the things that must be fulfilled by the government so that people can carry out activities using proper facilities without any obstacles that could endanger people who walk on foot. The research method used in this study is normative juridical or normative approach, namely a method that examines a problem using the basis of existing rules such as laws. This method is used to see whether a problem being studied is in line with existing rules. In this study, it was found that existing rules are not in line with reality in the context of fulfilling pedestrians. Pedestrians have not felt the facilities provided fully because they are hindered by several factors. So, when viewed from the perspective of Islamic religious knowledge. This has not caused benefits in the community.